Restorative justice informed criminal justice social work and probation services - Kirkwood, Steve (Probation journal, 2019)
Despite the growth of restorative justice (RJ) research, theory and practice, little work has explored its implications for criminal justice social work (CJSW) and probation services. Our analysis demonstrates that an RJ ‘lens’ transforms the view of CJSW, enlarging the scope to help people make amends for harm, magnifying the role for victims of crime, refocusing on the meaningfulness of reparative acts and clarifying the role of communities in reintegration. Our vision of RJ informed CJSW and probation services offers a way of shifting practice to help people repair harm, make good and move on with their lives.